Disain Pltu Skala Kecil Berbahan Bakar Batubara - Hoetman, Agus Rusyana (JTM-ITI (Jurnal Teknik Mesin ITI), 2017)
AbstractThis paper discussed the design of small-scale Coal Steam Power plant. Where Combustion technology for the small-scale that is fluidized bed and stoker will be compared. Particulate pollution, SO2 control devices, and facilities for water and waste water treatment are also presented. The Heatrate on a small scale power plant will not be the same as a large scale, this is due to the small scale coal power plant boiler efficiency is lower (83-85%) and alsoÂ  need much greater power auxiliarry (10-15%) [4]. The efficiency of small-scale coal power unit on average is only about 22-23%. Construction of small scale coal mine mouth steam Power plant outside Java-Bali is increasing, this is because the price of fuel relatively cheaper and improvement of the operation can now be more competitive than diesel power plant. But there are some aspects of the design in coal small scle Power plant needs to be proved, given the coal power plant Â has several major components that require more complex requirements than diesel.Keywords: power plant, fluidized bed, stoker, pollution.